Blockchain and smart contracts: a game changer in mediation? - Mak, Charles Ho Wang; Mante, Joseph (Asian journal on mediaton, 2023)
In light of accelerating technological innovation and shifts in dispute resolution paradigms, this article elucidates the transformative potential of blockchain technology and smart contracts in mediation. The paper posits that these advancements offer an innovative framework for dispute avoidance and a more efficient, transparent process for resolving conflicts, particularly in commercial settings. The article critically assesses the inherent challenges and argues that overcoming these obstacles necessitates a multi-stakeholder approach, encompassing legislative measures, educational initiatives, and technological enhancements. It ultimately contends that blockchain and smart contracts hold the capacity to significantly reshape the landscape of mediation.
https://rgu-repository.worktribe.com/output/2085489/blockchain-and-smart-contracts-a-game-changer-in-mediation https://rgu-repository.worktribe.com/output/2085489
Keywords: Blockchain technology; Dispute resolution; MARD; Mediación; Mediation; Mediação; Médiation; Smart contracts

Standing in international investment and trade disputes - Ossa, Ralph; Staiger, Robert W.; Sykes, Alan O. (Journal of International Economics, 2023)
International investment agreements employ dispute settlement procedures that differ markedly from their counterparts in trade agreements. A prominent and controversial difference arises with respect to the issue of “standing”: Who has the right to complain to adjudicators about a violation of the agreement? While trade agreements limit standing to the member governments (state-to-state dispute settlement), investment agreements routinely extend standing to private investors as well (investor-state dispute settlement). We develop parallel models of trade and investment agreements and employ them to study this difference. We find that the difference in standing between trade and investment agreements can be understood as deriving from the fundamentally different problems that these agreements are designed to solve. Our analysis also identifies some important qualifications to the case for including investor-state dispute settlement provisions in investment agreements, thereby offering a potential explanation for the strong political controversy associated with these provisions.
Keywords: Bilateral investment agreements; Investments; Investor-State Dispute Settlement; State-to-state dispute settlement; Trade agreements; Trade dispute

Legal Reconstruction of Dispute Settlement Between Importers and Exporters International Law Perspective - Pristha Utama, Wahyu; Tri, Lazarus; Setiyono, Joko (Journal of Xi'an Shiyou University, Natural Sciences Edition, 2023)
Reconstruction of dispute resolution law between importers and exporters from an international law perspective. The purpose of this study is to analyze: 1) How does the law of dispute resolution between importers and exporters perspective international law? 2) How is the implementation of the recommendations of the dispute resolution bodies of the World Trade Organization from an international law perspective? The research method used is normative juridical with a statutory approach, concept approach, and case studies. The results showed that: 1) Import export is a series of company activities that begin with an agreement. The agreement is the result of previous activities carried out by exporters and importers, namely in the form of supply and demand. The agreement is poured into a sales contract which is an agreement between exporters and importers to trade goods in accordance with mutually agreed conditions and each party binds itself to carry out all obligations incurred. 2) The series of processes undertaken in dispute settlement at the WTO consist of 4 processes, including: Mandatory Consultation between disputing parties to reach a settlement approved by the parties, Application for the establishment of a Panel, the Appellate Body, and the implementation and implementation of recommendations and provisions endorsed by the DSB.
Keywords: Dispute Resolution; Exporter; Importer; International Law; Reconstruction

Party autonomy and judicial participation in commercial arbitration: recalibrating the role of Nigerian courts. - Aduloju, Bamikole Martins (Robert Gordon University, 2023)
Courts and arbitration tribunals aim to resolve disputes and make enforceable decisions in their distinctive way. However, unlike courts, tribunals lack state enforcement power to function independently. Consequently, arbitrating parties have had to approach the courts for various supports. However, while supporting arbitration, the Nigerian courts have been criticised for overwhelmingly undermining party autonomy. Thus, the determination of the extent to which Nigerian courts should participate in arbitration remains topical. This research reviewed the current regime governing the scope and limits to the court's roles in arbitration in Nigeria, aiming to find out the problematic areas where the court's roles have been a leeway to undermine party autonomy. The research found that the current practice in Nigeria generally observes party autonomy as an affirmative stance by the Nigerian courts and laws. It further found the areas where the Nigerian system has, nevertheless, created some leeway for the courts to undermine party autonomy. These include (i) the narrow phrasing and interpretation of Section 34 of the Act and some specific provisions, and their failure to set out a definite limit to courts' roles in arbitration, (ii) the application of the concept of constitutional supremacy which has been interpreted to allow Nigerian courts to participate in all cases including arbitration and override parties' agreement, (iii) absence of Institutionalised tracking and periodic recalibration of the relationship between the courts and arbitration, and (iv) judicialisation of administrative roles of the courts in arbitration. To this end, a legal and analytical review of these problematic issues was conducted, particularly using some elements of the legal comparative approach to analyse the problems in the light of the related practices in some similar or advanced jurisdictions such as the United Kingdom, Ghana and Malaysia. Lessons were drawn from the analysis. Short- and long-term recommendations were, therefore, made for law reforms in Nigeria, particularly towards recalibrating the court's roles in arbitration such as to wedge the loopholes in the system without which recalcitrant parties and jurists could take advantage to undermine party autonomy.
Keywords: Arbitrage; Arbitragem; Arbitration; Autonomy; Court systems; Judiciary; Tribunals

The impact of blockchain and smart contracts on dispute settlement: a case for mediation. - Mak, Charles Ho Wang; Mante, Joseph (Dispute settlement: the past, present and future dimensions, 2023)
The research is premised on two important developments, accelerating technological innovation and shifts in dispute resolution paradigms. These advancements offer an innovative framework for dispute avoidance and a more efficient, transparent process for resolving conflicts, particularly in commercial settings. To make this case, we use blockchain technology and smart contracts as technological exemplars, and mediation as an example of dispute resolution mechanism that can be positively impacted by the use of the relevant technology. The potential of these technologies to promote dispute avoidance and the emerging legal frameworks for resolving blockchain technology and smart contract disputes were also explored. We also examine how blockchain technology and smart contracts can be integrated into the mediation process, the advantages, challenges, and possible solutions.
https://rgu-repository.worktribe.com/output/2086138/the-impact-of-blockchain-and-smart-contracts-on-dispute-settlement-a-case-for-mediation
Keywords: Blockchain technology; Dispute resolutions; Disputes; Smart contacts; Technological innovation

Transparency in international arbitration: balancing the need for openness with the need for confidentiality - Mak, Charles Ho Wang; Rohatgi, Akshita (ACICA review, 2023)
International arbitration is often presented as an efficient and appropriate alternative to domestic court systems for resolving conflicts. For international arbitration to be effective, it is essential that the procedure adopted be open and accountable. This article will discuss the significance of openness in international arbitration and how it may promote justice, foster trust, and avoid corruption and misbehaviour.
https://rgu-repository.worktribe.com/output/2255845/transparency-in-international-arbitration-balancing-the-need-for-openness-with-the-need-for-confidentiality
Keywords: Corruption; International Arbitration; Justice; Misbehavour; Transparency; Trust

Confidentiality in International Commercial Arbitration: Is it an Accepted Principle, and if so, Should the Model Law Regulate it? - Kenny, Caroline Majella (Monash University, 2023)
This thesis examines two research questions: first, whether confidentiality in international commercial arbitration (‘ICA’) is an ‘accepted principle’, and second, if the answer to the first question is positive, whether confidentiality should be regulated by the United Nations Commission on International Trade Law (‘UNCITRAL’) Model Law on International Commercial Arbitration (1985), with amendments adopted in 2006 (‘Model Law’) and how such a provision would be framed. To place the questions in context, there is empirical evidence that confidentiality is expected by users of ICA but despite this expectation there appears to be no uniform approach on confidentiality in national laws and institutional rules.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; UNCITRAL Arbitration Rules; UNCITRAL Model Law

The efficacy of commercial arbitration, law and practice Lesotho - Thethe-Chitja, Makabelo (National University of Lesotho, 2023)
The success of commercial arbitration law and practice is achieved as a result of several factors. The purpose of the study was to investigate whether efficacy of commercial arbitration, law and practice in Lesotho is hindered by the legal framework which does not conform to the United Nations Commission Trade Law on International Commercial Arbitration, UNCITRAL Model Law. Examining such other factors as support of the courts and government, the study specifically investigated the impact of lack of education about commercial arbitration for the business community and unregulated arbitrators on the efficacy of the commercial arbitration, law and practice in Lesotho. With the use of the desk reviews and interviews as data collection methods for this study, the evidence obtained has revealed that efficacy of the commercial arbitration, law and practice in Lesotho is hampered by the law which is outdated and inconsistent with the UNCITRAL Model law. As such, support for the mechanism by the courts has been found to be at stake or adversely affected. Lack of support from the government and that of awareness campaigns about the mechanism for the business community have also been noted for constraining the efficacy of the commercial arbitration, law and practice in the country. Further noticeable from the findings include limited commitment from the legal profession and unregulated arbitrators, both of which could have significantly obstructed the mechanism. The study thus concludes that there is an urgent need for law reforms and concerted commitment from the relevant stakeholders to help towards achieving efficacy of the commercial arbitration, law and practice in Lesotho.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Lesotho

Addressing the Legitimacy Crisis of Investment Arbitration Through its Harmonization with World Trade Organization Law - Seifi, Seyed Jamal; Veis Karami, Mahdi (Public Law Researsh, 2023)
International investment law is facing a legitimacy crisis, in which to tackle, substantial efforts are being made in structural and procedural areas. The first step to overcoming this crisis is identifying the roots of it. The lack of a dynamic balance between public and private interests is one of the main factors creating this legitimacy crisis in this legal system.[1] This paper focuses on the changes in the investment arbitration jurisprudence to create this balance. The findings of this paper can explain one of the convergence points of international trade and investment law. Such a claim is based on the evolution of international trade law in facing a similar legitimacy issue and the structural-procedural approach of this legal system in balancing public and private interests as an ultimate solution to the crisis.[2] From this perspective, one of the major factors in creating a legitimacy crisis in both legal systems is the dominance of the paradigm for preference of private interests; and one of the convergence points of international trade and investment law has been to replace it by accepting the paradigm of creating a dynamic balance between competing goals.[3] This paper examines this convergence in arbitral jurisprudence.IntroductionIn recent years, the legitimacy crisis of the regime of international investment law and, as a result, the investor-state dispute settlement system has been one of the most important and controversial topics in the academic environment and the practice of states consequently, serious efforts in various fields to tackle this crisis have begun. According to this paper, choosing an arbitration mechanism modeled on international commercial arbitration to resolve disputes between host states and foreign investors can be evaluated as a wrong and hasty action that, regardless of its factors and contexts, has changed the nature and function of this system over time.[4] It should be noted that the main factor in such consequences is how this dispute resolution system is used which, contrary to the accepted model, always puts the host states in a "respondent" position in possible future disputes and, as a result, disrupts the balance expected in any international dispute settlement system. On this basis, the confrontation of the host state's sovereign competence in ensuring public interests with the foreign investors’ ability to challenge this competence is brought into the spotlight: currently, within the regime of international investment law, host states have only responsibilities and obligations in contrast to extensive and exclusive rights and privileges recognized for foreign investors, and this can be considered as the most important factor disturbing the said balance. The main issue in this field is to analyze the role of the investment arbitral tribunals in creating such a balance. In this regard, the authors, by focusing on the nature of investment treaties, and the relations between the parties in investment disputes and with emphasis on the general legal regime governing international investment, consider creating a dynamic balance between public and private interests to be the key to solving the crisis. They emphasize that; As long as the rights and obligations of the parties to the dispute are based on imbalanced grounds, the change in nature of the disputes and the function of the system -as the main roots of this legitimacy crisis - will remain. In this remark, it is very important to focus on the two-sided nature (public-private) of the relationships established in the framework of investment treaties. The relationship between the host state and the foreign investor is created within the framework of investment treaties and in light of fundamental differences from purely private relationships in international commercial arbitration.[5] Note that any dispute arising from this relationship is affected by its inherently public nature governed by public international law.[6] Thus, a purely private attitude towards these relations does not seem viable. As Ian Brownlie has stated in the case of SME v. the Czech Republic, it can lead to ignoring some of the basic elements of the relevant investment treaty.[7] In other words, the right and duty of the host state in protecting and promoting public interests is a fundamental part of this relationship, and any indulgence of it leads to a serious disruption of the mentioned balance through which the system's legitimacy will be the first victim.It is clear that the main task of any dispute resolution system is to create such a balance, and on this basis, and compared to the WTO dispute resolution system, the role of the investment tribunals in this process is discussed. This jurisprudential convergence is in line with the goal of strengthening the legitimacy of the international investment law system as a whole.Based on the above, the first part of this paper focuses on the process of establishing the ISDS in international investment law and its characteristics, the factors of the crisis of legitimacy are analyzed with an analytical approach, while also explaining the nature of investment treaties and explaining the general legal regime governing international investment. Furthermore, the lack of a dynamic balance between public and private interests is emphasized as the main cause of the crisis. In the second part, while comparing the two legal systems of international trade and investment with a similar crisis of legitimacy, we will examine the interaction of investment arbitration with the WTO's jurisprudence in facing this crisis through a case study of several investment arbitral awards. [1]. David Gaukrodger, “The Balance between Investor Protection and the Right to Regulate in Investment Treaties: A Scooping Paperˮ, OECD Working Paper on International Investment 2017/02, at 4.[2]. Nicholas DiMascio & Joost Pauwelyn, “Non-Discrimination in Trade and Investment Treaties: Worlds apart or Two Sides of the Same Coin?”, AJIL, Vol. 102, No.1, (2008), at 89.[3]. Jurgen Kurtz and Sungioon Cho, “Convergence and Divergence in International Economic Law and Politics”, EJIL, Vol. 20, No. 1, (2018), at 187.[4]. Benedict Kingsbury & Stephan W. Schill, “Public Law Concepts to Balance Investor's Rights with State Regulatory Actions in the Public Interest - The Concept of Proportionalityˮ, In Schill Stephan W., International Investment Law and Comparative Public Law (UK: Oxford University Press, 2010) at 76. [5]. Crina Baltag, “Reforming The ISDS System: In Search of a Balanced Approach?ˮ, Contemporary Asia Arbitration Journal, Vol. 22, No. 2, (2019), at 285.[6]. Ibid.[7]. Andreas Kulick, “Sneaking Through Backdoor – Reflections on Public Interest in International Investment Arbitrationˮ, Arbitration International, Vol. 29, No. 3, (2013), at 438.
Keywords: Crisis of Legitimacy; International Investment Law; Investor-State Dispute Settlement; WTO; World Trade Organization

Rights and Obligations of the Parties Against International Arbitration Awards in Indonesia - Puspita, Lona; Budiono, Abdul Rachmad; Kusumadara, Afifah; Widagdo, Setyo (International Journal of Social Science Research and Review, 2023)
The position of international arbitration awards which is different from national arbitration awards and district court decisions causes differences in the rights and obligations of the parties to arbitral awards, especially those relating to legal remedies against awards. The formulation of the problem in this study is how are the rights and obligations of the parties to international arbitral awards in Indonesia. The research method used in this article is legal research using primary and secondary legal materials. The results of the study state that the rights possessed by the parties to international arbitral awards in Indonesia are related to legal remedies against decisions, namely corrections to these international arbitral awards. The corrections to the decisions here are not only limited to administrative corrections but also corrections related to the principal international arbitral awards made before the request for execution was registered at the Central Jakarta District Court. While the obligations of the parties to international arbitral awards are to carry out international arbitral awards in good faith.
Keywords: International Arbitration Award; Rights and Obligations

Introduction: International Adjudication and the Legacy of the Mixed Arbitral Tribunals - Ruiz Fabri, Hélène (The Mixed Arbitral Tribunals, 1919–1939: An Experiment in the International Adjudication of Private Rights, 2023)
This introduction provides the reader with a general characterization of the 39 Mixed Arbitral Tribunals (MATs) created by the 1919-1923 peace treaties to address disputes between private persons and between private persons and states as a result of the First World War. Noting that the rich literature published on the MATs was followed by near-silence after 1945, it mentions the numerous questions that they still raise today, before explaining how the various contributions to the book edited by the authors address them.

Third Party Funding in International Arbitration: A Critical Appraisal and Pragmatic Proposal - Sweify, Mohamed (Edward Elgar Publishing, 2023)
The author of Third Party Funding in International Arbitration challenges the structural inconsistencies of the current practices of arbitration funding by arguing that third party funding should be a forum of justice, rather than a forum of profit. The author introduces a new methodology with an alternative way of structuring third party funding to solve a set of practical problems generated by the risk of claim control by the funder.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitral justice; Arbitration; Claim control; Dispute outcome; Financement; Funders; Third Party Funding; Tiers

Investigation of Investor-State Arbitration Problems in Afghanistan - Nikzad, Nezamuddin; Anwari, Gulaqa (International Journal of Social Science Research and Review, 2023)
The main purpose of this research is to explain and identify the major Investor-State Arbitration (ISA) problems in Afghanistan. Afghanistan's government is committed to providing legal security for the resolution of foreign investment disputes. The dispute resolution system's assessment is very important for foreign investors because they pay special attention to the dispute resolution system and consider it a criterion for their investments. This research will be the first comprehensive study about the Investor-State Arbitration problems in Afghanistan. In the writing of this research, the library method has been used. To extract reasons, laws, books, articles, and reliable scientific sources have been used. Afghanistan is a good market for foreign investment because it has good investment opportunities in different sectors. Foreign investors can choose the easiest and best mechanisms, such as arbitration in their contracts to deal with disputes. But the resolution of foreign investment through arbitration has some problems, and sometimes foreign investors are facing challenges with the settlement of their disputes through arbitration internationally and domestically in Afghanistan.
Keywords: Arbitration; Dispute; Foreign Investment; Investigation in Afghanistan; Problems

Procedural powers of arbitrators in international arbitration- Real or perfunctory? - Mishra, Ajit Kumar (International Journal of Law, 2023)
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; International Arbitration; Lex arbitri; Procedural powers; Tribunal power

The Dilemma of International Arbitration Awards in Indonesia - Puspita, Lona; Budiono, Abdul Rachmad; Kusumadara, Afifah; Widagdo, Setyo (International Journal of Social Science Research and Review, 2023)
The final and binding nature of international arbitral awards results in the nullification of the rights of the parties to file legal remedies against the arbitral award, as is the case with decisions of national courts that can be appealed, appealed, or reviewed. However, Article 68 paragraph (2) of Law Number 30 of 1999 concerning arbitration and Alternative Dispute Resolution provides an opportunity for parties who refuse to recognize and implement an international arbitral award that can be appealed to, as well as Article 70 must also be explained that Article this applies only to national arbitrations. This of course creates legal uncertainty, disuse, and injustice for the parties. Therefore, what is highlighted in this research is what is the position of the final and binding international arbitration award in Indonesia. The research method used in this article is legal research using primary and secondary legal materials. The results of the research show that the position of international arbitral awards in Indonesia is not the same as the decisions of national courts because they cannot be appealed, cassated, and reviewed. Therefore, it is necessary to completely amend international arbitration arrangements by removing Article 68 paragraph (2) of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution in order to provide legal certainty, benefit, and justice for the parties.
Keywords: Award; Final and Binding; International Arbitration

Effective Conflict Management - International Chamber of Commerce (ICC DRS Publications, 2023)

The International Validity of Domestic Law in Investment-Treaty Arbitration - Jarrett, Martin (Arbitration international, 2023)
Keywords: Arbitrage; Arbitragem; Arbitration; Investment arbitration; Investments

Arbitrability of Intellectual Property Dispute: A Pragmatic Dispute Resolution Mechanism - Singh, Vaishali (International Journal of Science and Research, 2023)
Conventionally, conflicts over intellectual property rights have been addressed primarily in national courts. Nonetheless, there has been a considerable inclination towards arbitration in recent years. For example, the number of cases decided under the WIPO Arbitration and Mediation Rules is constantly increasing, and the number of specific IP-related arbitral institutions is rising as well. This is due, in part, to the territorially limited reach of state court procedures, which no longer match the needs of modern international commercial processes. The transition to arbitration is appropriate since arbitration is particularly well suited to settling intellectual property conflicts. Arbitration is a private process, which is especially beneficial in IP issues due to the sensitive nature of the material involved. Furthermore, specific knowledge is necessary to properly settle technological disputes, a challenge that might be overcome by choosing adequately competent arbitrators.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Intellectual property; WIPO (World Intellectual Property Rights Organization)

Effective strategies for resolving labour disputes in the corporate sector: Lessons from Nigeria and the United States - Uzougbo, Ngozi Samuel; Akagha, Onyinyechi Vivian; Coker, Julie Olajumoke; Bakare, Seun Solomon; Ijiga, Amina Catherine (World Journal of Advanced Research and Reviews, 2023)
The relationship between an employer and employee though governed by various laws and regulations can still at some point witness some disagreements and dispute. Labour disputes are not uncommon neither are they peculiar to a particular industry in a country. Usually, trade disputes are hinged on agitation of employees for compensation, good working conditions, job stability and agitation against unlawful termination or dismissal of from service. Over the years, employees have adopted different ways to exhibit their discomfort and grievances in order to convey their message such as strike actions, peaceful protest and so on. There’s no doubt that these disputes will drastically reduce the level of productivity and overall beneficial impact of the industries in the economic growth of the country. Hence, there’s a need to adopt strategies for resolving these labour disputes. Some industries have applied round table discussions, arbitration, mediation, collective bargaining as well as grievances remedial processes. This work will provide an overview of the causes of disputes in the corporate sector, examine the features of the Nigerian and United States disputes resolution system and also juxtapose the strategies for resolving labour disputes in the two countries. Furthermore, it will provide recommendations to effectively addressing labour issues within the business sector.
Keywords: ADR; Alternative dispute resolution; Industrial relations; Legislative Framework; Multi-door courthouse; Trade unions